Meningoencephalitis Bacterial DD Viral with Organic Mental Disorders - Ade Giriayu Anjani; Nadia Pramasari; Lelly Winduhani (Sean Institute, 2026)
Meningoencephalitis is inflammation that occurs in meninges and brain tissue. Symptoms encephalitis include fever, seizures, decreased consciousness. Meningoencephalitis can be caused by viral, bacterial, spirochete, fungal, protozoan infections. Based MSCT radiology examination head with coronal and sagittal slices reformatted axially with contrast, first result showed no infarction, bleeding, mass pressure effects on brain parenchyma, mild brain edema, second result no visible hypo/hyperdense lesions in sulci and gyri of brain parenchyma, slight thinning visible, ventricular system and cisterna normal, pons and cerebellum normal, there is no abnormal calcification visible and visible midline deviation, orbita, mastoid, right with left paranasal sinuses and calvaria is not visible. Normal, no osteolytic or osteoblastic processes visible. Based microbiological examination urine, cerebrospinal fluid with gram staining and aerobic culture as well as sensitivity testing, results showed that no aerobic or anaerobic germs were found. Laboratory examination, WBC > 12 103/µL, procalcitonin 0.163 ng/ml, CRP 6.22 mg/dl, based laboratory examinations which exceeded normal limits experienced by patient, inflammation and infection. Empiric antibiotic therapy for bacterial meningoencephalitis can use fluoroquinolones or cephalosporin ceftazidime, based good BBB penetration. Procalcitonin examination, blood culture, and lumbar puncture were performed again. Diagnosis meningoencephalitis is viral, then acyclovir in form injection used.